2020
DOI: 10.1093/infdis/jiaa739
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fatty Liver and Cirrhosis, Hepatocellular Carcinoma, and Hepatitis B Surface Antigen Seroclearance in Chronic Hepatitis B

Abstract: Background Chronic hepatitis B (CHB) and fatty liver (FL) are common, natural history data on concurrent FL and CHB (FL-CHB) are limited. This study aimed to evaluate the effect of FL on cirrhosis, hepatocellular carcinoma (HCC), and HBsAg seroclearance incidence in CHB patients. Methods In a retrospective cohort study of 6,786 adult CHB patients, we used propensity score matching (PSM) to balance the FL-CHB and non-FL CHB gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 47 publications
3
77
1
Order By: Relevance
“…To investigate how long SARS-CoV-2 viruses are stable in cell culture media at 4 °C, we thawed different stock aliquots of a SARS-CoV-2 (which were cryo-conserved at −80 °C, 1 × 10 8 TCID 50/ml ) at weekly intervals and stored them at 4 °C in cell culture medium for up to 160 days. Remarkably, using TCID 50 even after 160 days we were still able to detect considerable quantities of infectious virus (> 1 × 10 5 TCID 50 /ml, < 3 log reduction, data not shown), which was in line with previous findings demonstrating long-term survival under 4 °C [ 18 , 19 ].…”
Section: Resultssupporting
confidence: 90%
“…To investigate how long SARS-CoV-2 viruses are stable in cell culture media at 4 °C, we thawed different stock aliquots of a SARS-CoV-2 (which were cryo-conserved at −80 °C, 1 × 10 8 TCID 50/ml ) at weekly intervals and stored them at 4 °C in cell culture medium for up to 160 days. Remarkably, using TCID 50 even after 160 days we were still able to detect considerable quantities of infectious virus (> 1 × 10 5 TCID 50 /ml, < 3 log reduction, data not shown), which was in line with previous findings demonstrating long-term survival under 4 °C [ 18 , 19 ].…”
Section: Resultssupporting
confidence: 90%
“…There have been a few conflicting reports regarding the long‐term prognosis of CHB patients according to the co‐existing fatty liver. While several studies have reported associations of fatty liver with advanced liver fibrosis and/or HCC development in patients with CHB, 14‐19 others have failed to demonstrate such associations 20‐24 . In contrast to CHB, the effects of fatty liver on liver fibrosis in patients with CHC have been well characterised 14,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…One recent study showed that reduced hepatic steatosis was significantly associated with a higher risk of HCC in CHB infection 9 . Additionally, in a multi‐centre retrospective cohort of 7816 Asian patients with CHB, fatty liver was significantly associated with lower risks of cirrhosis and HCC 10 . In our CHB cohort (Search‐B cohort), we also found that patients with co‐existing fatty liver had significantly lower 5‐year incidence of HCC than those without fatty liver (2.0% vs 3.4%, P = 0.004) (Figure 1).…”
Section: Figurementioning
confidence: 52%